Highly Efficient and Reversible Covalent Patterning of Graphene: 2D-Management of Chemical Information - Wei, Tao; Kohring, Malte; Chen, Muqing; Yang, Shangfeng; Weber, Heiko B.; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie International Edition, 2020)
Patterned graphene-functionalization with a tunable degree of functionalization can tailor the properties of graphene. Here, we present a new reductive functionalization approach combined with lithography rendering patterned graphene-functionalization easily accessible. Two types of covalent patterning of graphene were prepared and their structures were unambiguously characterized by statistical Raman spectroscopy together with scanning electron microscopy/energy-dispersive X-ray spectroscopy (SEM-EDS). The reversible defunctionalization processes, as revealed by temperature-dependent Raman spectroscopy, enable the possibility to accurately modulate the degree of functionalization by annealing. This allows for the management of chemical information through complete write/store/erase cycles. Based on our strategy, controllable and efficient patterning graphene-functionalization is no longer a challenge and facilitates the development of graphene-based devices.
CRIS-Team WoS Importer:2020-02-11